PERBANDINGAN ALTERNATIF PENYELESAIAN SENGKETA NASABAH PERBANKAN KONVENSIONAL DAN SYARIAH SEBAGAI LEMBAGA PENYELENGGARA JASA KEUANGAN DI REPUBLIK INDONESIA - Stanis, Geraldo Adrian (Jurnal Yuridis, 2025)
This paper, using a juridical-normative method comparative law technique, discusses the consumer dispute resolution between conventional and sharia banking. The provision of financial services as a legal act of engagement cannot avoid disputes between the parties specifically between banking institutions and customers. Disputes between customers and banking institutions as providers of financial services need to be resolved by institutions that have absolute or relative authority in order to provide decisions legally binding. After determining the authority possessed by alternative dispute resolution institutions, each institution has formal norms in order to fulfill the sense of justice of justice seekers which differs between conventional and sharia banking. Through this article the author will conduct a comparative legal analysis of alternative methods for customer disputes resolution in conventional and sharia banking as financial service providers in the Republic of Indonesia.